Numerical investigation of the scale effect of hydrodynamic performance of the hybrid CRP pod propulsion system. (January 2016) - Wang, Zhan-Zhi; Xiong, Ying; Wang, Rui; Zhong, Chen-hua
Highlights: A method of estimating hydrodynamic performance of the hybrid CRP pod propulsion system at full scale was proposed. Scale effect of hydrodynamic performance of the hybrid CRP pod propulsion system was investigated numerically using RANS method combined with SST k  −  ω turbulence model and moving mesh method, and some phenomenons were found. An experimental investigation of hydrodynamic performance of the hybrid CRP pod propulsion system at model scale was performed to validate numerical results. Abstract: The scale effect of hydrodynamic performance of the hybrid CRP pod propulsion system was investigated numerically using the RANS method combined with SST k  −  ω turbulence model and moving mesh method. The pod resistance influence factor was introduced to represent the effect of wake field of CRP on the pod resistance. Results showed the pod resistance influence factor to be a function of the Reynolds number and revolution ratio. Representative function expression can be obtained by regression analysis using multiplication of multinomial polynomials and linear function. The standard ITTC 1978 extrapolation procedure can be utilized to predict hydrodynamic performance of forward propeller because of the slightness of the influence of the pod unit on the forward propeller. The thrust and torque coefficient influence factors of aft propeller were introduced, and they were found to represent the effect of wake field of forward propeller and blockage effect of the pod on the hydrodynamic performance of aft propeller. It shows that thrust and torque coefficient influence factors are independent of the Reynolds number and have a linear relationship with the revolution ratio. On this basis, a method of estimating the hydrodynamic performance was proposed for full scale propulsion system.